Neem leaves extract (Azadirachta indica A. Juss) on male reproductive system: a mini-review. (December 2019) - Seriana, I; Akmal, M; Darusman,; Wahyuni, S
Abstract: Neem ( Azadirachta indica A. Juss ) is the tropical plant of the family Meliaceae that has been used as medicine. Almost all parts, i.e., leaves, stems, bark, roots, seeds, and flowers can be used to medicate multiple diseases. Apart from medicine and other health benefits, neem is a very promising plant as it could be used to reduce the rate of population growth. The aim of this review is to figure out the effect of neem leaves on the male reproductive system which can be developed into safe and reversible male contraception. The article review used online databases to conduct keyword searches and investigate the active compounds in neem leaves that could serve as antifertility, the effect of neem leaves on reproductive hormones and spermatogenesis. Several studies show that neem leaves can affect the male reproductive system by interfering spermatogenesis, e.g., reducing the amount, motility, and morphology of the spermatozoa, affecting the structure and function of the testes which cause a decrease in the quality of spermatozoa. Abnormal spermatozoa could reduce spermatozoa ability to fertilize. Thus neem leaves can be proposed as male contraceptives.